Improving hospital operations management to reduce ineffective medical appointments. Issue 1 (1st January 2021) - Barretiri, Leandro; Gonçalves, Bruno S.; Lima, Rui M.; Dinis-Carvalho, José
Abstract: The main objective of this study is to meet management aspirations by promoting waste reduction and consequently improving patients` experience in a Portuguese public hospital. These aspirations include increasing hospital service quality in a continuous and efficient way. This management mindset uncovered divergences between medical appointment and magnetic resonance imaging (MRI) exam scheduling that were generating waste for both the hospital and patients. The main aspects considered in this study were the patients' medical expectations, the quality, and cost of service provided. One-year retroactive encrypted data from medical appointments and MRI requisitions were provided for the algorithm development. Outcomes obtained from the algorithm revealed a high percentage of medical appointments occurring without the respective MRI exam results. These outcomes exposed waste existence that was hitherto unknown by the administration. Thus, the main algorithm function is to analyze future data to previously alert ineffective medical appointments. This progress contributes to reducing wasted medical and patient time. In summary, the main contribution of this article is to allow hospital managers to cross-check data from different sectors to identify divergences in future medical consultations that require exams or results of clinical analysis.